(untitled) (Global Journal of Medical Research, 2022)
Simple diagnostic imaging (WHIS-RAD) and ultrasound are non-available for health workers practicing in low-resource developing nations. A low-tech approach rather than hi-tech is appropriate, with excellent clinical results. These adjuncts to the history and physical will lead to markedly improved clinical outcomes.